PROSUMERIC ACTIVITY OF CONTEMPORARY FINAL PURCHASERS VS. THEIR RELATIONSHIPS WITH OFFERORS - Agnieszka Baruk (Polityki Europejskie, Finanse i Marketing, 2020)
The article is of a theoretical and empirical nature. To prepare the theoretical part the available literature on marketing and consumer behaviour was cognitively and critically analysed. The results of the analysis allowed for identifying a knowledge gap and a research gap in this area. So far, purchaser activity in the context of relationships and image has not been analysed, especially in relation to offerors perceived as the initiators of communication and creation behaviours of purchasers. Therefore, the aim of the article was to define the significance of mutual relationships between purchasers and offerors in relation to the activity of final purchasers. A research hypothesis was verified: that the perception of offerors as the initiators of the activity of final purchasers differentiates the range of this activity. In order to achieve the goal and check the formulated hypothesis, a nationwide empirical research was conducted. The research involved a questionnaire for collecting primary data, which was afterwards statistically analysed by means of cluster analysis and the Kruskal-Wallis test. The results revealed that good relationships were important or very important for the majority of respondents. The perception of offerors was significant as far as the form of marketing activity for purchasers are concerned. However, it is possible to note statistically significant differentiation in the case of two forms of purchaser activity. So, the research hypothesis turned out to be valid only for these two forms.